Translation quality assessment past and present - House, Juliane (Routledge, 2015)
"Translation Quality Assessment has become one of the key issues in translation studies. This comprehensive and up-to-date treatment of translation evaluation makes explicit the grounds of judging the worth of a translation and emphazies that translation is, at its core, a linguistic art. Written by the author of the worlds best known model of translation quality assessment, Juliane House provides an overview of relevant contemporary interdisciplinary research on intercultural communication and globalization research, corpus and psycho- and neurolinguistic studies. House also acknowledges the importance of socio-cultural and situational context in which texts are embedded, and which need to be analysed when they are transferred through space and time in acts of translation but also highlights the linguistic art form of translation. The text includes a a newly revised and presented model of translation quality assessment which, like its predecessor, relies on detailed textual and culturally informed contextual analysis and comparison. The test cases also show that there are two steps in translation evaluation: firstly analysis, description and explanation; secondly, judgements of value, socio-cultural relevance and appropriateness. The second is futile without the first: to judge is easy, to understand less so. Translation Quality Assessment is an invaluable resource for students and researchers of Translation Studies and Intercultural Communication, as well as for professional translators"--Provided by publisher.